Genetic diversity of Streptococcus agalactiae from dairy cattle with mastitis in Argentina - Gerez, María Gabriela (2025)
Bovine mastitis is an important health problem in dairy cattle which affects the quality and yield of milk and causes significant economic losses in the dairy industry. Streptococcus agalactiae is a Gram-positive and zoonotic bacterium that causes clinical and subclinical contagious bovine mastitis. The main strategy for the control of this pathogen in dairy herds is the antimicrobial therapy. The aim of this study was to determine the genetic diversity of S. agalactiae using Multiple Locus Variable number tandem repeat -VNTR- Analysis (MLVA), serotypes, virulence factors (VF) and antimicrobial resistance (AMR) profiles and to compare the discrimination power of these different methods in strains isolated from cattle with mastitis in Argentinian dairy farms.Eighty-seven S. agalactiae isolates obtained from dairy cattle with mastitis in Argentina were analyzed. The detected serotypes were III, II and Ia. The most frequent virulence and AMR detected genes were cpsA, hylB, PI-2b, cylE, rib, spb1, and tetO and ermB respectively. A total of 36 VF + AMR profiles were detected with a discriminatory power of the method of Ds = 0.96. The MLVA based on six VNTRs showed 29 profiles with a Ds = 0.90. The analysis of VF + AMR + MLVA data together showed 59 profiles with an increased discriminatory power (Ds = 0.98).This study highlights that the MLVA is recommended to add to other methodologies in order to study epidemiological relationships in this species Although within each dairy farm there was a predominance of certain serotypes/virulence profiles, the characteristics did not show total homogeneity, as expected due to the contagious nature of the pathogen. This suggests the incorporation of animals from other herds at some point, a practice not uncommon among dairy farms in Argentina. By other hand, the detection of a same clone in the same farm in different periods confirms that S. agalactiae strains can persist on dairy farms for a long time.